CLINICAL AND MORPHOLOGICAL FEATURES OF HEREDITARY OVARIAN CANCER - K. B. Kotiv; T. V. Gorodnova; A. O. Ivantsov; A. G. Iyevleva; S. N. Aleksakhina; G. M. Manichas; A. S. Lisyanskaya; R. P. Salomatov; M. S. Shushaniia; M. V. Borodenko; L. D. Roman; G. I. Mikhailiuk; et al. (Сибирский онкологический журнал, 2017)
Germ-line mutations in BRCA1 and BRCA2 genes are the most established risk factors for hereditary breast and ovarian cancers. The purpose of the study was to analyze BRCA1/2 testing in ovarian cancer patients. Materials and methods. We analyzed 222 patients with ovarian cancer (OC) who underwent genetic testing. Results. Recurrent Slavic mutations in these genes were detected in 60/222 (27%) patients.104 patients lacked any clinical signs of hereditary form of the disease, however BRCA1/2 genetic defects were identified among 11 (11%) of these women. BRCA1/2-associated carcinomas were characterized by more advanced stage at diagnosis and predominance of high-grade serous histological tumor subtype. Conclusion. These results emphasize the need for BRCA1/2 testing for all patients with OC. BRCA1/2-associated carcinomas have clinical and pathological cgaracteristics, which should be considered while planning therapy.